1987
DOI: 10.1007/bf01914567
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic temperatures of non-isothermal rate signals of one-step processes

Abstract: Analytical expressions for the heights, and for the initial, the peak and the final temperature of the rate signals of bimolecular reactions, measured at constantly increased temperature, are derived. They are based on the specific time of the reaction, available from the activation data, and on the relative minimum rate used. DTA and non-isothermal u.v. absorption studies of 29 different organic reactions in solution reveal that the accuracy of the expressions is sufficient to reproduce the true position of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Fig. 15 describes the various quantities which appear in (32). The conductivity, u, is related to nc by the universal equation…”
Section: Simultaneous Measurements Of Tl and Tscmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 15 describes the various quantities which appear in (32). The conductivity, u, is related to nc by the universal equation…”
Section: Simultaneous Measurements Of Tl and Tscmentioning
confidence: 99%
“…15. The variables in (32) T -Lewandowski and McKeever [8] showed that in the generalized approach to TL and TSC (Section 2.5) one can evaluate Q ( T ) (17) by using the relation Q(T) = C (F + l)/ITL(T). (34) The coefficient C incorporates some constants the values of which are usually unknown.…”
Section: Simultaneous Measurements Of Tl and Tscmentioning
confidence: 99%
“…It is unity for n= 1, but depends on co for n ~ 1. (TCRC -Theory of Characteristic Rate Coefficients [13]; cf. [16,17,231).…”
Section: ( R )mentioning
confidence: 99%
“…For the M-strings, such effects are caused by the co-dependent term (uk)m in the denominator of Eq. (7), used for a correction of M [13,14,27]. For some -mostly consecutive -mechanisms, stationarities cannot really be reached for both limiting elements (e.g.…”
Section: Structure Of the Mcc-strings And Influence Of The Signal Parmentioning
confidence: 99%
See 1 more Smart Citation